Estimated Age Structure of Wolves in Northeastern Minnesota - Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2006)
Information about population age structures is useful to understand survival rates, longevity, and population turnover. However, little such information is available about wolf (Canis lupus) populations. Mech (1970) estimated age structures of wolf-population age structure from pup:adult ratios applying various demographic assumptions, but no direct information has been published to test his estimate. Mech et al. (1998) aged 94 live wolves darted in Denali National Park and Preserve, Alaska, USA, but the estimates of wolf ages were based on educated guesses because no technique was available for aging live wolves. Since then, Gipson et al. (2000) published criteria for aging live wolves based on tooth wear of known-aged animals. This method allows data to be gathered from populations of live animals, which can facilitate examination of the age structure of populations. My objective was to use this method to estimate the age structure of a population of wolves in the Superior National Forest (SNF) of northeastern Minnesota, USA.